2006
DOI: 10.1017/s0031182005009509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of four tanniferous plant extracts on thein vitroexsheathment of third-stage larvae of parasitic nematodes

Abstract: The anthelmintic properties of tanniferous plants and of their secondary metabolites represent one possible alternative to chemotherapy that is currently being explored as a means of achieving sustainable control of gastrointestinal nematodes in ruminants. Previous in vivo and in vitro results suggest that tanniferous plants can have direct anti-parasitic effect against different stages of nematodes. However, the mode of action of the bioactive plant compounds remains obscure. The objectives of the current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 31 publications
2
77
0
9
Order By: Relevance
“…The assay conducted in this study has been routinely used in other experiments. Bahuaud et al (2006), Brunet et al (2007), Alonso-Díaz et al (2008a, 2008b found retardation or inhibition of H. contortus and Trichostrongylus colubriformis larval exsheathment after incubation with tanniferous plant extracts. The assumption is that condensed tannins complex with the sheath proteins of nematodes, which have high proline content and prevent exsheathment (BRUNET et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The assay conducted in this study has been routinely used in other experiments. Bahuaud et al (2006), Brunet et al (2007), Alonso-Díaz et al (2008a, 2008b found retardation or inhibition of H. contortus and Trichostrongylus colubriformis larval exsheathment after incubation with tanniferous plant extracts. The assumption is that condensed tannins complex with the sheath proteins of nematodes, which have high proline content and prevent exsheathment (BRUNET et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The test was performed according to Bahuaud et al (2006). The extracts were diluted in phosphate buffer solution (PBS), and the concentration evaluated was 300 µg.mL -1…”
Section: Larval Artificial Exsheathment Assaymentioning
confidence: 99%
“…Studies in New Zealand (Niezen et al 1995, 1998, United Kingdom (Athanasiadou et al 2000a, b, Marley et al 2003, France (Paolini et al 2003, Bahuaud et al 2006 and United States (Min and Hart 2003) have shown that some plant species that contain CTs may reduce the degree of parasite infections and improve sheep and goat performance. Although the underlying mechanisms for such beneficial effects have not been determined, both direct (Athanasiadou et al 2000a, b) and indirect (Aerts et al 1999, Waghorn andMolan 2001) effects of CTs on parasites in the gut were suggested to be behind these effects.…”
mentioning
confidence: 99%
“…Artemisia absinthium, Chenopodiumgraveolens, Gymnospermaglutinosum, Limpiacritridora, Populusalba and Thymus vulgaris, have an activity of 500 mg/L respectively (Tables 1, 2). These results were obtained by means of different repeated tests in the vitro model [17,18].…”
Section: Resultsmentioning
confidence: 99%